Pengaruh Minat Belajar Siswa terhadap Hasil Belajar Matematika di Sekolah Inpres Bumi Sagu - Moh. Rizky Aditya; Eva Setya Rini; Nova Riyanti Hidayat; Fitra Amalia; Afrianti (JURNAL DIKDAS, 2026)
This study aims to determine the effect of learning interest on the mathematics learning outcomes of elementary school students. The study employed a quantitative approach using a simple linear regression analysis method to examine the relationship between learning interest as the independent variable (X) and mathematics learning outcomes as the dependent variable (Y). The research was conducted on sixth-grade students at Sekolah Inpres Bumi Sagu with a sample of 30 students. Data were collected through the distribution of Likert-scale questionnaires to measure students’ learning interest and documentation of daily mathematics test scores to assess learning outcomes. The results of the analysis showed that the regression equation obtained was Y = 62.6207 + 0.1511X, with a coefficient of determination (R²) value of 0.0205. This indicates that learning interest contributed only 2.05% to the variation in students’ mathematics learning outcomes, while the remaining 97.95% was influenced by other factors outside the research variables. The significance test results showed a t-count value of 0.766 with a significance value of 0.095 (> 0.05), indicating that learning interest did not have a significant effect on students’ mathematics learning outcomes. Nevertheless, learning interest still showed a positive relationship with mathematics learning outcomes. Therefore, improving mathematics learning outcomes is influenced not only by learning interest but also by other factors such as learning motivation, teaching methods, and the learning environment.